2015
DOI: 10.1111/1365-2435.12519
|View full text |Cite
|
Sign up to set email alerts
|

Mutualism effectiveness of a fungal endophyte in an annual grass is impaired by ozone

Abstract: 1.Ozone is an increasing tropospheric contaminant of climate change. Exposure to ozone may affect the symbiotic relationship between plants and beneficial microorganisms. In particular, the herbivore resistance mechanism conferred by fungal endophytes (defensive mutualism) may be affected, as any of the ozone-triggered effects (such as elicitation of defence mechanisms against biotrophic fungi or oxidative stress in the apoplastic space) may target the symbiont. 2. Symbiotic and non-symbiotic Lolium multifloru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 82 publications
(216 reference statements)
7
44
0
Order By: Relevance
“…However, we found that infected A. sibiricum had significant resistance to L. migratoria , which suggests that apart from endophyte-conferred alkaloid defense, additional mechanisms such as endophyte-mediated changes in host defense are likely to be implicated in endophyte-host-insect interactions. Similar results have been reported recently by Ueno et al (2016), who found that ozone level did not affect alkaloid concentration but rather significantly affected aphid resistance of infected Lolium multiflorum .…”
Section: Discussionsupporting
confidence: 91%
“…However, we found that infected A. sibiricum had significant resistance to L. migratoria , which suggests that apart from endophyte-conferred alkaloid defense, additional mechanisms such as endophyte-mediated changes in host defense are likely to be implicated in endophyte-host-insect interactions. Similar results have been reported recently by Ueno et al (2016), who found that ozone level did not affect alkaloid concentration but rather significantly affected aphid resistance of infected Lolium multiflorum .…”
Section: Discussionsupporting
confidence: 91%
“…The infection frequency was determined by sampling 50 seeds of each population and endophyte status (high and low infection). Even though in this study we did not quantify alkaloid plant concentration, Ueno et al (2016) recently reported that plant concentration of loline derivatives (Nacetylnorloline, N-formylloline and N-acetylloline) in infected plants ranged between 200 and 300 lg g À1 of plant in this population. Positive samples showed the presence of non-branching intercellular hyphae (Bacon & White 1994).…”
Section: Experimental Site Grass Populations and Steersmentioning
confidence: 78%
“…Lucero endophyte-infected seeds were obtained from the endophytic individuals of an original population with %53% infection, and the endophyte-free seeds, from the non-infected plants of the same original population. Even though in this study we did not quantify alkaloid plant concentration, Ueno et al (2016) recently reported that plant concentration of loline derivatives (Nacetylnorloline, N-formylloline and N-acetylloline) in infected plants ranged between 200 and 300 lg g À1 of plant in this population. Feliciano endophyte-infected seeds were obtained from an original population with 100% infection, and the endophyte-free seeds, from the same original population from which the endophyte was removed by an ageing treatment.…”
Section: Experimental Site Grass Populations and Steersmentioning
confidence: 78%
See 2 more Smart Citations